2022
DOI: 10.3390/ijerph19053138
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Perspectives on Determinants Avoidable Hospitalizations: Development and Validation of a Questionnaire

Abstract: Ambulatory care sensitive conditions (ACSC) can be avoided through effective care in the ambulatory setting. Patients are the most qualified individuals to express the social and individual contexts of their own experience. Thus, understanding why potentially preventable hospitalizations occur is important to develop patient-centred policies or interventions that may reduce them. This study aims to develop and validate a questionnaire to capture the patients’ perspective on the causes of the hospitalizations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“… 38 All tools assessed neighborhood or physical environment risks, while nine assessed healthcare access. 38 Sarmento et al 39 developed a questionnaire on determinants of potentially avoidable hospitalization, mainly covering disease self‐management, social support, health literacy, health status, and lifestyle at the individual level, and healthcare access and environmental characteristics at the contextual level. Although social risk screening tools are available in the literature, 40 , 41 there is a paucity of appropriate and comprehensive instruments for social risks that may have a greater impact on hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“… 38 All tools assessed neighborhood or physical environment risks, while nine assessed healthcare access. 38 Sarmento et al 39 developed a questionnaire on determinants of potentially avoidable hospitalization, mainly covering disease self‐management, social support, health literacy, health status, and lifestyle at the individual level, and healthcare access and environmental characteristics at the contextual level. Although social risk screening tools are available in the literature, 40 , 41 there is a paucity of appropriate and comprehensive instruments for social risks that may have a greater impact on hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…Estudos demonstram uma associação positiva entre a TC e a qualidade de vida, e resultados negativos relativos à utilização inadequada dos serviços de urgência e readmissões potencialmente evitáveis, quando não são desenvolvidas estratégicas estruturadas de TC (Alqenae et al, 2020;Opper et al, 2019;Sarmento et al, 2022).…”
Section: Discussionunclassified
“…Para melhorar o valor em saúde, é essencial definir indicadores para obtenção de resultados que sustentem melhores práticas e apoiem os políticos, gestores e equipas na compreensão da eficiência e dos desafios da implementação de intervenções no âmbito do processo de TC. A definição e monitorização desses indicadores são fundamentais para avaliar a efetividade e a eficiência das intervenções em TC, permitindo a identificação de áreas de melhoria e a tomada de decisão baseada em evidências (Kampstra et al, 2018;Sarmento et al, 2022). A utilização desses indicadores também pode contribuir para a avaliação da sustentabilidade e dos custos das intervenções em TC, garantindo a alocação eficiente dos recursos em saúde (Ng & de Colombani, 2015).…”
Section: Discussionunclassified
“…In general, the higher the PCC level, the higher the patient's and doctor's satisfaction and the higher the quality and safety of medical care (23)(24)29). People with complicated health problems tend to have a USC; some studies reported that PCC, along with a USC, reduces preventable hospitalization and improves health outcomes (24,(30)(31). Only one study has reported the positive effect of a USC on the PCC of patients with disabilities (26), and to the best of our knowledge, there are no other studies on the direct effect of PCC on the PPH of patients with disabilities.…”
Section: Introductionmentioning
confidence: 99%